Eye tracking as feedback tool in physics teacher education - Schweinberger, Matthias; Watzka, Bianca; Girwidz, Raimund (Frontiers in Education, 2023)
The ability to direct pupils’ attention on relevant information during the experimentation process is relevant for all science teachers. The objective of this article is to investigate the effects of using eye tracking visualizations of pupils’ visual attention as a feedback tool on physics student teachers' ability to direct attention during the presentation of experiments. Many eye tracking studies in the field of learning use eye movement recordings to study the effectiveness of an instructional design by varying cues or the presentation format. Another important line of research relates to study the teacher's gaze in a real classroom setting (mobile eye tracking). We are using eye tracking here in a completely new and innovative way: Eye tracking is deployed as a feedback tool for student teachers showing them the effects of their verbal instructions when trying to direct their pupils’ attention. The study is based on a mixed method approach and is designed as a single factor quasi-experiment with pre-post measurement. Teacher students work on the concept of "silent videos”; they record their verbal instructions to the video and pupils in school then watch these videos while their eye movements are tracked. The resulting eye movements are then reflected together with the teacher students and serve as the basis for individual feedback on the teacher student’s ability to control attention in class. In addition, they are asked individually about their experiences in participant interviews. The competences of the student teachers in moderating the set-up and the demonstration of an experiment were assessed and the student teachers' experiences were collected in interviews. Eye tracking as a feedback tool brings the effectiveness of their actions directly to the teacher students', so that they experience a higher level of self-efficacy as a result. The overall concept of "silent videos" incl. eye tracking as a feedback tool enables targeted training of the verbal guidance of the pupils’ attention during the presentation of demonstration experiments.